Pupillary reactivity to negative stimuli prospectively predicts recurrence of major depressive disorder in women. (27th September 2016) - Kudinova, Anastacia Y.; Burkhouse, Katie L.; Siegle, Greg; Owens, Max; Woody, Mary L.; Gibb, Brandon E.
Abstract: There is a large body of research supporting the association between disrupted physiological reactivity to negative stimuli and depression. The present study aimed to examine whether physiological reactivity to emotional stimuli, assessed via pupil dilation, served as a biological marker of risk for depression recurrence among individuals who are known to be at a higher risk due to having previous history of depression. Participants were 57 women with a history of major depressive disorder (MDD). Pupil dilation to angry, happy, sad, and neutral faces was recorded. Participants' diagnoses and symptoms were assessed 24 months after the initial assessment. We found that women's pupillary reactivity to negative (sad or angry faces) but not positive stimuli prospectively predicted MDD recurrence. Additionally, we found that both hyper‐ and hypopupillary reactivity to angry faces predicted risk for MDD recurrence. These findings suggest that disrupted physiological response to negative stimuli indexed via pupillary dilation could serve as a physiological marker of MDD risk, thus presenting clinicians with a convenient and inexpensive method to predict which of the at‐risk women are more likely to experience depression recurrence.